COVID-19: Systemic risk and response management in the Republic of Korea - Yong-kyun Kim (Elsevier, 2021)
This study aimed to investigate the different kinds of risks associated with the novel coronavirus infection in the Republic of Korea and how those risks have been changed by the countermeasures taken by the Korean authorities and citizens. To this end, the authors explored the official database of the Korea Centers for Disease Control and Prevention (KCDC) in order to extract risk-related data from January 2020 to April 2021, and then identified the disaster risks and countermeasures from the government press briefings and news media in the same period. Consequently, this study identified three important approaches to enhance the infectious disease response management. First, the government has to respond immediately, even when they lack information and knowledge about the new type of risk. Second, a multi-sectoral response must be prepared to cope with systemic risks. Third, the government should prioritize transparency, inclusive risk governance, and innovative technologies during the initial response stage against risks with high uncertainty and novelty. Aside from these approaches, the types of risks were divided into four categories based on the response measures: anticipated risk against which countermeasures can be planned in advance, lingering risk against which adaptive response should be taken promptly, amplified risk, and emerging risk; the last two risks require the established plan to be modified drastically in order to secure higher-level engagement and additional resources. Finally, the authors proposed a risk management flow that can be applied to an in-depth analysis of the intersection between risk and response.